Two different cases of postoperative symptomatic common carotid artery involvment in type A aortic dissection - Droeser, Raoul A (BMJ Case Rep, 2012)
Postoperative common carotid artery occlusion after reconstruction for type A aortic dissection can lead to major neurological morbidity. Surgical strategy to re-establish the cerebral perfusion depends on the time of onset of neurological deficits in this otherwise life-threatening disease. We present two cases with neurological deficits after replacement of the ascending aorta for a type A dissection treated with two different surgical strategies. In both cases, prompt surgical interventions improved neurological outcome.